Biocement: green building-and energy-saving material - Chu, Jian; Ivanov, Volodymyr M.; Stabnikov, Victor; He, Jia; Li, Bing; Naemi, Maryam (My University, 2012)
Cement and chemical grouts have often been used for soil strengthening. However, high cost, energy consumption, and harm to environment restrict their applications. Biocement could be a new green building- material and energy-saving material. Biocement is a mixture of enzymes or microbial biomass with inorganic chemicals, which can be produced from cheap raw materials. Supply of biocementing solution to the porous soil or mixing of dry biocement with clayey soil initiate biocementation of soil due to specific enzymatic activity. Different microorganisms and enzymes can be used for production of biocement.
Keywords: biocement; biocementation; enzymes; microorganisms; біоцемент; біоцементація; фермент; мікроорганізми; биоцемент; биоцементация; микроорганизмы; кафедра біотехнології і мікробіології